A population of primary afferent sensory neurons mediates pain relief through nocifensive coping behavior in mice - Daichi Sueto; Sawako Uchiyama; Teruaki Ono; Moeka Watanabe; Misuzu Sekine; Yuto Nishida; Kohei Nomaki; Yuto Shibata; Ryoichi Tashima; Kazuki Fujimori; Yasuharu Nakashima; Makoto Tsuda (Proceedings of the National Academy of Sciences, 2026)
When exposed to noxious cutaneous stimuli, animals exhibit nocifensive behaviors, including rapid defensive reflexes that limit tissue damage and subsequent coping behaviors—most commonly licking of the affected area—that alleviate pain. Despite its ubiquity, the neural mechanism underlying pain relief through licking remains poorly understood. Here, we demonstrate that Npy2r-Cre + primary sensory neurons in the dorsal root ganglion (DRG), a population of Aβ fibers that includes touch-sensitive, rapidly adapting low-threshold mechanoreceptors, are critical for this process. Mice lacking Npy2r-Cre + neurons exhibited a significant prolongation of coping behavior duration, but not bout frequency, following intraplantar injection of capsaicin or formalin. Conversely, optogenetic activation of Npy2r-Cre + neurons produced attenuating effects on irritant-induced pain. Electrophysiological analyses revealed that Npy2r-Cre + neurons form functional synaptic connections with neurons in the substantia gelatinosa of the spinal dorsal horn (SDH) and that their activation suppressed C fiber-evoked excitation of neurons in lamina I of the SDH, a region implicated in nociceptive transmission to the brain. Together, these findings identify Npy2r-Cre + DRG neurons as a key neural substrate for gating nociceptive transmission in the SDH and mediating pain relief through coping behaviors.